Evaluating Glyphosate Exposure Routes and Their Contribution to Total Body Burden: A Study Among Amenity Horticulturalists. Issue 2 (4th January 2019) - Connolly, Alison; Coggins, Marie A; Galea, Karen S; Jones, Kate; Kenny, Laura; McGowan, Padraic; Basinas, Ioannis
Abstract: Objective: To evaluate determinants of dermal and inadvertent ingestion exposure and assess their contribution to total body burden among amenity horticultural users using glyphosate-based pesticide products. Methods: A dermal and inadvertent ingestion exposure assessment was completed alongside a biomonitoring study among amenity horticultural workers. Linear mixed effect regression models were elaborated to evaluate determinants of exposure and their contribution to total body burden. Results: A total of 343 wipe and glove samples were collected from 20 workers across 29 work tasks. Geometric mean (GM) glyphosate concentrations of 0.01, 0.04 and 0.05 µg cm −2 were obtained on wipes from the workers' perioral region and left and right hands, respectively. For disposable and reusable gloves, respectively, GM glyphosate concentrations of 0.43 and 7.99 µg cm −2 were detected. The combined hand and perioral region glyphosate concentrations explained 40% of the variance in the urinary (µg l −1 ) biomonitoring data. Conclusion: To the author's knowledge, this is the first study to have investigated both dermal and inadvertent exposure to glyphosate and their contribution to total body burden. Data show the dermal exposure is the prominent route of exposure in comparison to inadvertent ingestion but inadvertent ingestion may contribute to overall body burden. The study also identified potential exposure to non-pesticide users in the workplace and para-occupational exposures.